Nghiên cứu hệ epoxy DER-331 đóng rắn bằng metyltetrahydrophtalic anhydrit (MTHPA) để chế tạo vật liệu compozit tiên tiến. Phần I - Nghiên cứu chế độ đóng rắn và tính chất hệ DER-331/MTHPA. - Chương, Bùi; Thọ, Trần Như; Anh, Lê Hoài; Khiêm, Vũ Đình; Liên, Đinh Thị (Vietnam Journal of Chemistry, 2012)
The curing of DER-331 epoxy system with methyltetra hydrophtalic anhydride as curing agent, DMP-30 as catalyst has been studied for different ratio of curing agent, catalyst, curing tempreature and time by measuring gel content. The aim of this work was to focused on studying the effect of the anhydride and DMP-30 concentration on the gel content of the system. By varying the tempreature and time, the gel content also was found to depent on the curing tempreature and time The result shows that the gel content of this system reach the highest (95%) when the anhydride/catalyst/epoxy molar ratio was at 0.75/0.028/1. The optium curing tempreture and time were at 115oC within 3 hours. The mechanical and chemical resistance properties of this system were also characterized.